Modelling methane hydrate stability changes and gas release due to seasonal oscillations in bottom water temperatures on the Rio Grande cone, offshore southern Brazil. (February 2020) - Braga, R.; Iglesias, R.S.; Romio, C.; Praeg, D.; Miller, D.J.; Viana, A.; Ketzer, J.M.
Abstract: The stability of methane hydrates on continental margins worldwide is sensitive to changes in temperature and pressure conditions. It has been shown how gradual increases in bottom water temperatures due to ocean warming over post-glacial timescales can destabilize shallow oceanic hydrate deposits, causing their dissociation and gas release into the ocean. However, bottom water temperatures (BWT) may also vary significantly over much shorter timescales, including due to seasonal temperature oscillations of the ocean bottom currents. In this study, we investigate how a shallow methane hydrate deposit responds to seasonal BWT oscillations with an amplitude of up to 1.5 °C. We use the TOUGH + HYDRATE code to model changes in the methane hydrate stability zone (MHSZ) using data from the Rio Grande Cone, in the South Atlantic Ocean off the Brazilian coast. In all the cases studied, BWT oscillations resulted in significant gaseous methane fluxes into the ocean for up to 10 years, followed by a short period of small fluxes of gaseous methane into the ocean, until they stopped completely. On the other hand, aqueous methane was released into the ocean during the 100 years simulated, for all the cases studied. During the temperature oscillations, the MHSZ recedes continuously both horizontally and, in a smaller scale, vertically, until a permanent and a seasonal region in MHSZ are defined. Sensitivity tests were carried out for parameters of porosity, thermal conductivity and initial hydrate saturation, which were shown to play an important role on the volume of methane released into the ocean and on the time interval in which such release occurs. Overall, the results indicate that in a system with no gas recharge from the bottom, seasonal temperature oscillations alone cannot account for long-term gas release into the ocean. Highlights: Methane release from oceanic hydrates due to seasonal temperature variations mostly in the aqueous phase over 100 years. Stability zone recedes downslope over time but most of it remains unaltered. Methane release rate and stability zone changes sensitive to initial saturation, porosity and thermal conductivity.